(untitled) (Al-Mansour Journal, 2023)
Software cost estimation is the process of predicting the amount of effort required to build a software system . Models provides one or more mathematical algorithms that compute cost as a function of a number of variables, size is primary cost factor in most models and can be measuring using lines of code (LOC). Models used to estimate cost of the software, the SLIM is used to estimate the constraint model and SLIM suitable to for large projects and has fewer parameters needed to generate an estimate. In this paper implement SLIM Model equation over the two different projects, we make the analysis of these two projects and conclusion relation between effort and duration and this relation is increase with increase the size of project.